Use of alkaline phosphatase fusions to study protein secretion in Bacillus subtilis. - Payne, M S (1991)
We have constructed a vector designed to facilitate the study of protein secretion in Bacillus subtilis. This vector is based on a translational fusion between the expression elements and signal sequence of Bacillus amyloliquefaciens alkaline protease and the mature coding sequence for Escherichia coli alkaline phosphatase (phoA). We show that export of alkaline phosphatase from B. subtilis depends on a functional signal sequence and that alkaline phosphatase activity depends upon secretion. The vector design facilitates the insertion of heterologous coding sequences between the signal and phoA to generate three-part translational fusions. Such phoA fusions are easily analyzed by monitoring alkaline phosphatase activity on agar plates or in culture supernatants or by immunological detection. Exploitation of this methodology, which has proven to be extremely useful in the study of protein secretion in E. coli, has a variety of applications for studying protein secretion in B. subtilis.